The teacher as a 'colony': a case study of agentive responses to 'colonising' education policy in Vietnam. Issue 1 (2nd January 2018) - Saito, Eisuke; Atencio, Matthew; Khong, Thi Diem Hang; Takasawa, Naomi; Murase, Masatsugu; Tsukui, Atsushi; Sato, Manabu
Abstract: Neo-liberal educational policies that are being implemented globally work to foster competition among schools and teachers, as well as among children. In this situation, teachers must often come to accept the dominant representations of curricular policy developed by higher authorities. In this study, a case study design is used to describe how one school in Vietnam shifted away from this state of 'colonisation' by reforming the school under the framework of lesson study for learning community (LSLC). This paper subsequently argues that there is a need for school-level policies that democratise school culture and practices, resisting the negative impacts of colonising policies.